A deep intronic splice variant of the COL4A5 gene in a Chinese family with X-linked Alport syndrome - Qian, Pei; Bao, Ying; Huang, Hui-mei; Suo, Lei; Han, Yan; Li, Zhi-juan; Zhang, Min (Frontiers in Pediatrics, 2023)
Background: X-linked Alport syndrome (XLAS) is caused by pathogenic variants in COL4A5 and is characterized by progressive kidney disease, hearing loss, and ocular abnormalities.The aim of this study was to identify gene mutations in a Chinese family with XLAS, confirm a diagnosis, and provide an accurate genetic counseling. Methods: The proband was a 5-year-old male with microscopic hematuria and a family history of renal disease in 5 relatives.His relatives had microhematuria with or without proteinuria. His maternal uncle developed renal failure at the age of 35 years. He was evaluated by renal biopsy,whole-exome sequencing (WES) and whole-genome sequencing (WGS) for Alport syndrome. RT-PCR and cDNA Sanger sequencing were performed on RNA extracted from the skin of the proband. Then, a splicing reporter minigene assay was used to examine the effect of the variation on the splicing of the primary transcript in transfected cells. Results: Pathological examination of the kidney of the proband revealed diffuse thinning of the glomerular basement membrane, and immunofluorescence analysis indicated normal expression of the α5 chain in the basement membrane. No phenotype-associated candidate variant was detected in the proband via WES. A novel deep intronic COL4A5 variant (c.385–716G>A), which is segregated with disease in this family, was identified using WGS. In-vitro minigene assay and in-vivo RT-PCR analysis demonstrated that the variant could produce both normal and abnormal transcripts. The abnormal transcripts showed that the variant activated a cryptic splice site, introducing a 147 bp pseudoexon into the mRNA sequence and consequently generating a premature termination codon (p.G129Afs*38) and leading to frameshifting and truncation of the α5 (collagen IV) protein. Conclusion: This is the first report of the novel c.385–716G>A splicing mutation in the COL4A5 gene，which illustrates the importance of performing WGS to find additional mutations in WES-negative patients with highly suspected forms of genetic diseases. The same results obtained from the in-vitro and in-vivo splicing experiments confirm the consistency between the minigene assay and RT-PCR analysis. In addition，this study highlights the importance of functional analysis in diagnosis and genetic counseling in AS.